Spironolactone Protects against Diabetic Cardiomyopathy in Streptozotocin-Induced Diabetic Rats. (14th October 2018) - Liu, Wenjuan; Gong, Wei; He, Min; Liu, Yemei; Yang, Yeping; Wang, Meng; Wu, Meng; Guo, Shizhe; Yu, Yifei; Wang, Xuanchun; Sun, Fei; Li, Yiming; et al.
Abstract : Spironolactone (SPR) has been shown to protect diabetic cardiomyopathy (DCM), but the specific mechanisms are not fully understood. Here, we determined the cardioprotective role of SPR in diabetic mice and further explored the potential mechanisms in both in vivo and in vitro models. Streptozotocin- (STZ-) induced diabetic rats were used as the in vivo model. After the onset of diabetes, rats were treated with either SPR (STZ + SPR) or saline (STZ + NS) for 12 weeks; nondiabetic rats were used as controls (NDCs). In vitro, H9C2 cells were exposed to aldosterone, with or without SPR. Cardiac structure was investigated with transmission electron microscopy and pathological examination; immunohistochemistry was performed to detect nitrotyrosine, collagen-1, TGF- β 1, TNF- α, and F4/80 expression; and gene expression of markers for oxidative stress, inflammation, fibrosis, and energy metabolism was detected. Our results suggested that SPR attenuated mitochondrial morphological abnormalities and sarcoplasmic reticulum enlargement in diabetic rats. Compared to the STZ + NS group, cardiac oxidative stress, fibrosis, inflammation, and mitochondrial dysfunction were improved by SPR treatment. Our study showed that SPR had cardioprotective effects in diabetic rats by ameliorating mitochondrial dysfunction and reducing fibrosis, oxidative stress, and inflammation. This study, for the first time, indicates that SPR might be a potential treatment for DCM.